56.1k views
5 votes
(1 point) Find f'(1) if 6x (f(x))^4 +9x^3 f(x) = 78 and f(1) = -2​

(1 point) Find f'(1) if 6x (f(x))^4 +9x^3 f(x) = 78 and f(1) = -2​-example-1

1 Answer

4 votes

Answer:

42

Explanation:


6x (f(x))^(4)+9 x^(3) f(x)=78\\6x (f(1))^(4)+9 x^(3) f(1)=78\\6x(-2)^(4)+9 x^(3) (-2)=78\\f(x) = 6x(16)-18 x^(3)=78\\f'(x)=96-54x\\for x=1: f'(1)=96-54(1)=42

User Jogloran
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.